Academics as knowledge entrepreneurs - Brustureanu, Bogdan (2018)
This is an exploratory study aimed at translating concepts developed in the frame of commercial entrepreneurship studies to the university setting. Analogy is used in a particular manner that is to look for structural similarities between commercial entrepreneurship and the way knowledge is created and organized. The first step is to introduce the notion of academic opportunity. This becomes the basis for opening up a new perspective by introducing a new discourse in the practice of entrepreneurship, the academic discourse. The next step is to discuss the role of academic networks and their possible connections with the network approach in the business formation. The final part of the article contains three examples illustrating the notions introduced and discussed in the previous sections. - Reproduced.
Keywords: Knowledge management